Agricultural productivity and public expenditures in Sub-Saharan Africa - Allen, Summer L.; Qaim, Matin (International Food Policy Research Institute, 2012)
National governments, especially in sub-Saharan Africa, have limited budgets and are forced to make difficult funding decisions regarding the provision of social services and the support of agricultural programs. These provisions can play a critical role in rural incomes and agricultural production but due to data constraints, the effects of different types of social services on agricultural productivity in this region have not been analyzed in detail. This research provides indication that certain types of social services can influence agricultural production efficiency using the currently available data and multiple empirical methods. Specifically, it estimates the role of social services in the efficiency of input use for agricultural production, using both Stochastic Frontier Analysis and a Structural Equation Model. Ultimately, our conclusions are substantially limited by data constraints, but provide some indication that certain types of social services can influence agricultural production efficiency for a select set of African countries